2022
DOI: 10.1542/peds.2021-053537
|View full text |Cite
|
Sign up to set email alerts
|

RSV Epidemiology in Australia Before and During COVID-19

Abstract: BACKGROUND AND OBJECTIVES: COVID-19 public health measures have altered respiratory syncytial virus (RSV) epidemiology, resulting in an unseasonal summer epidemic in Australia in 2020. We aimed to determine if the shifted RSV epidemic was more severe compared with previous years or if age-specific changes were associated with the resurgence. METHODS: Through this multicenter study, we analyzed routinely collected datasets fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
88
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 21 publications
16
88
4
2
Order By: Relevance
“…Our study indicated that the severity of the delayed RSV seasons during COVID-19 in Shanghai was decreased, as evidenced by less frequent respiratory failure and severe LRTI cases than before, which was similar with the studies conducted in Australia and France, characterized by fewer hospitalizations and ICU admissions ( Fourgeaud et al, 2021 ; Foley et al, 2022 ; Saravanos et al, 2022 ). However, the impacts of the delayed RSV season on patients might vary in different settings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study indicated that the severity of the delayed RSV seasons during COVID-19 in Shanghai was decreased, as evidenced by less frequent respiratory failure and severe LRTI cases than before, which was similar with the studies conducted in Australia and France, characterized by fewer hospitalizations and ICU admissions ( Fourgeaud et al, 2021 ; Foley et al, 2022 ; Saravanos et al, 2022 ). However, the impacts of the delayed RSV season on patients might vary in different settings.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we observed an unusual increase of the RSV detection rate in the summer of 2021 in Shanghai. Interestingly, the abnormal reemergence of RSV during COVID-19 was also observed during the summer months in both northern hemisphere countries including Japan, America, Canada, Israel, Italy ( Public Health Agency of Canada, 2021 ; Ujiie et al, 2021 ; Weinberger Opek et al, 2021 ; Camporesi et al, 2022 ; The US Centers for Disease Control and Prevention, 2022 ), and southern hemisphere countries including Australia and New Zealand ( Agha and Avner, 2021 ; Anglemyer et al, 2021 ; Foley et al, 2021 , 2022 ; Dolores et al, 2022 ; Saravanos et al, 2022 ). Hence, our findings reflected a global phenomenon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As the pandemic progressed, other respiratory viruses were shown to circulate off-season, frequently during a period of SARS-CoV-2 decline, a phenomenon likely driven by changing weather patterns, other prevailing competing viruses in the ecosystem and possibly limited use of mitigating measures such as masks and social distancing [ 27 ]. One such example is respiratory syncytial virus, which occurred off-season in the summer of 2021 in the United States, Japan and Australia, also coinciding with a low COVID-19 case load [ 28 , 29 , 30 ]. In South Africa, a similar phenomenon was observed where influenza circulated off-season [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, the pandemic shifted the epidemiology and impact of other respiratory viruses for the pediatric population. 3 For instance, respiratory syncytial virus, an aggressive pathogen in infants, reached an unprecedented peak in the summer–fall of 2021. It is important to remember that even before the pandemic, respiratory illnesses were the top cause of hospitalization and death in children.…”
mentioning
confidence: 99%